2024
DOI: 10.3390/ijms25021117
|View full text |Cite
|
Sign up to set email alerts
|

Focusing on Ischemic Reperfusion Injury in the New Era of Dynamic Machine Perfusion in Liver Transplantation

Gabriela Chullo,
Arnau Panisello-Rosello,
Noel Marquez
et al.

Abstract: Liver transplantation is the most effective treatment for end-stage liver disease. Transplant indications have been progressively increasing, with a huge discrepancy between the supply and demand of optimal organs. In this context, the use of extended criteria donor grafts has gained importance, even though these grafts are more susceptible to ischemic reperfusion injury (IRI). Hepatic IRI is an inherent and inevitable consequence of all liver transplants; it involves ischemia-mediated cellular damage exacerba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 153 publications
0
1
0
Order By: Relevance
“…It has been suggested that using NMP after the initial SCS period facilitates the regeneration of impaired cellular metabolic processes [112]. Assessment of graft function is based on analysis of selected parameters, including hemodynamic stability, bile production, and perfusate lactate clearance [113]. However, to date, there has been no standardization of diagnostic biomarkers to enable clinical evaluation of grafts [114].…”
Section: Perfusion Methods Considerationsmentioning
confidence: 99%
“…It has been suggested that using NMP after the initial SCS period facilitates the regeneration of impaired cellular metabolic processes [112]. Assessment of graft function is based on analysis of selected parameters, including hemodynamic stability, bile production, and perfusate lactate clearance [113]. However, to date, there has been no standardization of diagnostic biomarkers to enable clinical evaluation of grafts [114].…”
Section: Perfusion Methods Considerationsmentioning
confidence: 99%